1984
DOI: 10.2307/3281632
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Complement by Tetrathyridia of Mesocestoides corti: Enhancement by Antibodies from Infected Mice and Lack of Effect on Parasite Viability

Abstract: Tetrathyridia of the cestode Mesocestoides corti were isolated from the peritoneal cavity of infected mice. The parasites activated guinea pig and mouse complement (C) in vitro by both the classical and alternative pathways as shown by quantitative C fixation and crossed immunoelectrophoresis. The ability of tetrathyridia to activate mouse C was enhanced by preincubating the parasites in serum obtained from mice infected with M. corti. Antibodies of the IgG1 class, an immunoglobulin found in profoundly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Indeed, it was shown that macrophages and giant cells from granulomas loose their receptors, particularly those for IgG (Mariano et al, 1977). Toye et al (1984) revealed that activation of complement did not play an essential role in the restriction of M. vogae growth in mice, indirectly supporting our fi ndings. We further evaluated the capacity of naive and post-infection peritoneal macrophages and monocytes to internalize non-opsonized particles.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, it was shown that macrophages and giant cells from granulomas loose their receptors, particularly those for IgG (Mariano et al, 1977). Toye et al (1984) revealed that activation of complement did not play an essential role in the restriction of M. vogae growth in mice, indirectly supporting our fi ndings. We further evaluated the capacity of naive and post-infection peritoneal macrophages and monocytes to internalize non-opsonized particles.…”
Section: Discussionsupporting
confidence: 84%